Effect of nZVI/biochar nanocomposites on Cd transport in clay mineral-coated quartz sand: Facilitation and rerelease - Shi Zhou (Elsevier, 2021)
The development and application of nano-biochar synthesized by ball milling technology is still challenging in the field of environmental remediation because of its higher activity with pollutants. The purpose of this study was to investigate the transport behavior of two kinds of biochar nanoparticles (nanobiochar (NBC) and nZVI-modified nanobiochar (nZVI-NBC)) and Cd2+ in clay mineral (kaolinite, illite, and montmorillonite)-coated quartz sand columns. The interaction between biochar nanoparticles and Cd2+ in saturated porous media was studied in cotransport experiments. Then, the effect of biochar nanoparticles on the release of Cd2+ in contaminated media was explored by elution experiments. The cotransport experiments showed that the mobility of Cd2+ was enhanced by two kinds of biochar nanoparticles, while the transport of biochar was limited due to the presence of Cd2+. The elution experiments showed that the transport of biochar nanoparticles can be inhibited by Cd2+ previously immobilized in the sand column, and Cd2+ can be rereleased by biochar nanoparticles. The rerelease ability of nZVI-NBC to Cd2+ is weaker than that of NBC because nZVI is more easily retained in the sand column after oxidation, thus strengthening the immobilization of Cd2+. In general, the recoveries of NBC, nZVI-NBC and Cd2+ in saturated porous media were reduced by the presence of clay minerals. The experimental results describing the stability of biochar nanoparticles in sand columns are consistent with those predicted by the Derjaguin-Landau-Verwey-Overbeek theory. The transport behavior of Cd2+ and biochar nanoparticles in sand columns can be well simulated by advection-dispersion-reaction. These findings reveal the interaction between biochar nanoparticles and heavy metals in the soil environment and provide new insights into the transport and fate of environmental remediation materials and pollutants in the underground environment.